PENGARUH MANAJEMEN LABA DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE DENGAN POLITICAL CONNECTION SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Basic Materials yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Dewi Ratri Rahmawati; Abdul Rohman (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of earnings management proxied by absolute discretionary accruals (DA), transfer pricing proxied by related party transactions (RPT), and tax avoidance proxied by effective tax rate (ETR), with political connection serving as a moderating variable. This research sample consists of secondary data from basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, selected using the purposive sampling method. Data analysis was conducted using a quantitative approach through multiple linear regression and moderated regression analysis (MRA) assisted by IBM SPSS Statistics 25 software. The results indicate that earnings management does not have a significant effect on tax avoidance, whereas transfer pricing has a positive and significant effect on tax avoidance. Meanwhile, political connection is unable to moderate the relationship between earnings management and tax avoidance, as well as the relationship between transfer pricing and tax avoidance.